Exercise and Stress in At-Risk Women during Pregnancy and Postpartum. Issue 4 (July 2021) - Guo, Yuqing; Kehoe, Priscilla; Pimentel, Pamela; Rousseau, Julie; Axelin, Anna; Rahmani, Amir M.; Dutt, Nikil
Abstract: Purpose: We aimed to understand the relationship between exercise and stress among socioeconomically at-risk women who participated in a home visitation service during pregnancy and postpartum. Methods: A mixed-methods design was used to support and supplement quantitative data using qualitative data. Convenience sampling was used to collect data from at-risk women via questionnaires and follow-up interviews. The Perceived Stress Scale was used to assess stress. Frequency and duration of exercise were assessed based on the American College of Obstetricians and Gynecologists exercise guidelines. Regression analyses examined the association between stress and exercise controlling for covariates. Content analysis was used to understand women's stress management experiences. Results: N = 114 women completed the questionnaire and a subgroup of 11 received follow-up interviews. Greater frequency of exercise was significantly associated with lower levels of stress. Approximately one-third of women reported experiencing significant stress. Talking to their husband or partner was the most used and exercise was the least used coping strategy. Many women recognized the importance of managing stress and benefits of exercise, but were hindered by barriers such as feeling tired, preventing them from exercising. Clinical Implications: A personalized and safe exercise program has the potential to be a low-cost stress management strategy for women during pregnancy and postpartum. Abstract : Exercise during pregnancy and postpartum may be a stress-reducing activity. In this study, 114 women participating in a home visit program offered their thoughts and experiences about the potential benefits of exercise in reducing stress via questionnaires and detailed interviews. Perinatal nurses can suggest exercise to women during pregnancy and postpartum as one way to promote their health and decrease stress.